A124 GASTRIC RETENTION IN CAPSULE STUDIES – IS AN ENDOSCOPY ALWAYS REQUIRED?. (4th March 2021) - Nassiri, S; Ou, G; Galorport, C; Enns, C A; Enns, R A
Abstract: Background: Capsule endoscopy (CE) is a non-invasive procedure for evaluating small bowel (SB) disorders but is limited by the completion rate. Gastric retention (GR), whereby the capsule remains in the stomach for the duration of the recording, can contribute to incomplete examinations given CE's finite battery life. Although this may be mitigated by using real-time imaging and/or endoscopic placement of capsule into the SB, such strategies require additional resource allocation. While other risk factors associated with incomplete examinations are well known, GR is not often discussed in the literature. Aims: To describe the management and outcomes of patients with GR. We hypothesize that most patients with previous gastric retention of the capsule, without known obstruction, will pass the capsule normally through the stomach with a second attempt without requiring endoscopic placement into the duodenum. Methods: Case series of patients with GR at a tertiary care centre in Vancouver, Canada. Prior to CE, all patients had undergone appropriate investigations to exclude obstructive pathology. All patients ingested 2L of polyethylene glycol-based bowel preparation the evening prior to the procedure and were fasting after midnight. Ingestion of the capsule occurred at 0700h. In patients who required repeat CE due to previous GR, capsule progress was assessed via real-time imaging at 1–2 hrs. If the capsule had not entered the SB by three hours, an attempt at endoscopic advancement of the capsule into the duodenum was made and/or endoscopic placement of capsule was arranged for a later date. Results: GR was found in 21 (2%) of 1024 patients between 09/2015 - 09/2020. The mean age of patients with GR was 58 ± 20.9 years (48% female). The most common indication for CE in this group was obscure gastrointestinal bleeding ( n = 12, 57%). The mean Charlson Comorbidity Index was 2.9 ± 3.5. Thirteen patients (62%) had a history of abdominal/pelvic surgery. Fourteen patients (67%) had repeat CE, nine (64%) of which passed into the SB without endoscopic assistance. Of those requiring endoscopic assistance ( n = 5), two had successful endoscopic placement, one required dilation of pyloric stenosis prior to successful placement, one failed endoscopic placement due to stenotic gastroplasty orifice, and another required upper endoscopy for further evaluation. None experienced delayed adverse events related to GR. Conclusions: CE can be safely repeated in patients with previous GR; most capsules will pass through the stomach spontaneously when repeated and do not require endoscopic assistance. Funding Agencies: None